Construction of core-shell Fe3O4@GO-CoPc photo-Fenton catalyst for superior removal of tetracycline: The role of GO in promotion of H2O2 to OH conversion. (15th April 2022) - Huang, Xiaohan; Xiao, Jianfei; Yi, Qing; Li, Dejian; Liu, Chenrui; Liu, Yun
Abstract: A novel core-shell structured Fe3 O4 @GO-CoPc magnetic catalyst, which is with magnetite (Fe3 O4 ) as the core, graphene oxide (GO) as the interlayer and cobalt-phthalocyanine (CoPc) as the shell, was successfully prepared and used as a heterogeneous photo-Fenton catalyst for tetracycline (TC) degradation in this work. The core-shell structure of the catalyst was confirmed by XRD, FTIR, SEM and TEM. BET and magnetic hysteresis loops measurements indicated that Fe3 O4 @GO-CoPc catalyst owned large specific surface area and could be easily recovered under an external magnetic field. Meanwhile, the experimental results of TC degradation demonstrated that the photo-Fenton efficiency of Fe3 O4 @GO-CoPc was excellent. When the reaction time was 120 min, TC could be degraded almost completely in the photo-Fenton system with Fe3 O4 @GO-CoPc. The high photo-Fenton catalytic activity of Fe3 O4 @GO-CoPc could be resulted from the effective transfer of photo-generated electrons between CoPc and Fe3 O4 by GO. Moreover, the main reaction species, OH, O2 -, 1 O2 and h +, were verified by the analysis of active species in this system. Finally, the mechanism analyses and quantitative analysis results of active species indicated that the introduction of GO accelerated the cycle between Fe(II) and Fe(III) as well as improved the effective utilization of H2 O2 (the efficiency of conversion of H2 O2 to OH). Highlights: Fe3 O4 @GO-CoPc was synthesized by simultaneous immobilized and synthesized methods. Fe3 O4 @GO-CoPc showed superior photo-Fenton catalytic activity and stable structure. Fe3 O4 @GO-CoPc system enhanced the conversion efficiency of H2 O2 to .OH.